EP-182 The predictive significance of neutrophil-to-lymphocyte ratio in cholecystitis: a systematic review and meta-analysis. (9th August 2022) - Millward, Alex; Kler, Aaron; Taib, Adnan; Hajibandeh, Shahab; Hajibandeh, Shahin; Asaad, Peter
Abstract: Aims: The aim of this review was to examine whether neutrophil-to-lymphocyte ratio (NLR) can predict the presence of cholecystitis and distinguish between simple and severe cholecystitis. Methods: A systematic literature search was performed. Risk of bias was assessed using the Newcastle-Ottawa Scale. Random effects model was used to calculate mean difference (MD) in two situations: (a) no cholecystitis versus cholecystitis and (b) simple versus severe cholecystitis. Receiver operating characteristic (ROC) curve analysis was performed to determine cut-off values of NLR for the above situations. Results: Ten retrospective studies comprising of 2827 patients were included. 327 had no cholecystitis, 2100 had simple cholecystitis and the remaining 400 had severe cholecystitis. NLR was significantly higher in acute cholecystitis compared to "no cholecystitis" (MD = 8.05 (95% CI 7.71–8.38), p < 0.01) and severe cholecystitis when compared with simple cholecystitis (MD = 3.14 (95% CI 1.26–5.02), p < 0.01). For patients with cholecystitis compared to those without cholecystitis, an NLR cut-off value of 2.98 was identified (AUC = 0.90). Logistic regression analysis confirmed NLR > 2.9 was an independent predictor of cholecystitis (OR 36.0, p = 0.006). In simple versus severe cholecystitis, an NLR cut-off value of 8.5 was identified (AUC = 0.73). Binary logistic regression analysis suggested an NLR > 8.5 was not an independent predictor of severe cholecystitis (OR 6.5 p = 0.090). Conclusion: NLR is significantly higher in patients with cholecystitis of any severity compared to patients without cholecystitis. Moreover, NLR can predict acute cholecystitis. However, NLR cannot predict the severity of disease due to inadequately powered studies.